THE EFFECT OF FOOT SOAKING THERAPY WITH RED GINGER BAKED ON HIGH BLOOD PRESSURE IN PREGNANT WOMEN AT THE GUNTUR GARUT COMMUNITY HEALTH CENTER IN 2025 - Pebriyanti Rahayu; Fenni Valianda Amelia Ramadhan (Jurnal Penelitian Progresif, 2026)
During pregnancy, various events often occur, including hypertension. Therefore, hypertension needs to be treated and controlled. Hypertension in Pregnancy (HDK) is a major cause of maternal death. Pregnancy is a physiological process. The definition of pregnancy is fertilization or the union of spermatozoa and ovum, followed by nidation or implantation. The process of changes that occur will cause an imbalance of estrogen and progesterone hormones in the mother's body during pregnancy, including hypertension. The condition of a pregnant woman with hypertension is when she experiences an increase in systolic or diastolic blood pressure greater than 140/90 mmHg. Hypertension treatment can be done pharmacologically and non-pharmacologically. The purpose of this study was to determine the effect of providing foot soak therapy with red ginger decoction on high blood pressure in pregnant women at the Guntur Garut Community Health Center in 2025, using a quasi-experimental method, with a one-group pretest-posttest research design. The sampling technique used purposive sampling with a sample size of 20 respondents. The average blood pressure of hypertensive clients before the foot soak therapy with red ginger decoction was 165.16 mmHg while the average blood pressure after the foot soak therapy with red ginger decoction was 159.63 mmHg, with a t-test obtained a p-value of 0.001. Conclusion: There is an effect of providing foot soak therapy with red ginger decoction on high blood pressure in pregnant women at the Guntur Community Health Center in 2025. It is recommended for hypertensive pregnant women in an effort to treat and overcome hypertension can be done with foot soak therapy with warm red ginger decoction and maintain a diet.